Proceedings of the 14th International ACM SIGACCESS Conference on Computers and Accessibility 2012
DOI: 10.1145/2384916.2384932
|View full text |Cite
|
Sign up to set email alerts
|

How do professionals who create computing technologies consider accessibility?

Abstract: In this paper, we present survey findings about how user experience (UX) and human-computer interaction (HCI) professionals, who create information and communication technologies (ICTs), reported considering accessibility in their work. Participants (N = 199) represented a wide range of job titles and nationalities. We found that most respondents (87%, N = 173) reported that accessibility was important or very important in their work; however, when considerations for accessibility were discussed in an open-end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 14 publications
0
16
1
1
Order By: Relevance
“…Previous work has discussed how it is important to include representative users when conducting research and that an induced situational impairment does not constitute the same experience as a permanent disability [48]. However, temporary and situational accessibility challenges can be used as a method to create empathy within developers [46] and also exists as an area where design challenges exist due to the increasing range of situations where technology is now used [52]. In our work we have shown that developers are aware of a large number of permanent challenges that users face within the areas of visual, communication, physical, cognitive, and emotional accessibility.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Previous work has discussed how it is important to include representative users when conducting research and that an induced situational impairment does not constitute the same experience as a permanent disability [48]. However, temporary and situational accessibility challenges can be used as a method to create empathy within developers [46] and also exists as an area where design challenges exist due to the increasing range of situations where technology is now used [52]. In our work we have shown that developers are aware of a large number of permanent challenges that users face within the areas of visual, communication, physical, cognitive, and emotional accessibility.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…The latter studies reported implementation rates, which were about 50 % of less. Some of these studies were conducted with general software professionals (Antonelli et al, 2018;Cao & Loiacono, 2018;Enabled Group, 2005;Lopes et al, 2010;Rosson et al, 2005;Tangarife & Mont'alvao, 2006;Vollenwyder et al, 2019) while some included more specific domain of participants such as accessibility, HCI or UX specialists (Inal et al, 2019;Putnam et al, 2012;Yesilada et al, 2015Yesilada et al, , 2012. Many of them also included participants from various countries (Enabled Group, 2005;Lazar et al, 2004;Lopes et al, 2010;Yesilada et al, 2012) or some others focused on one country such as Brazil (Antonelli et al, 2018;Freire et al, 2008;Inal et al, 2019;Tangarife & Mont'alvao, 2006), Switzerland (Vollenwyder et al, 2019) and Turkey (Inal et al, 2019).…”
Section: Related Studiesmentioning
confidence: 99%
“…Nevertheless, it is important to keep in mind that Web accessibility is a very complex and broad topic. This means that not everybody has to know it fully [49]. For native applications with standard controls, the human interface guidelines from the host operating system are mandatory in case developers and want to create a graphical user interface (GUI) in line with the operating system style [50].…”
Section: Applying Existing E-accessibility Patterns To Develop Accessmentioning
confidence: 99%